Observation of BRACU on the test result and visual inspection report on the fire protection pipes and instruction to start the piping work immediately - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the observation of BRACU new campus project on the test result and visual inspection report on the fire protection pipes and instruction to start the piping work immediately.